2014
DOI: 10.1002/pc.22869
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recycling number on the mechanical, chemical, thermal, and rheological properties of PBT/PC/ABS ternary blends: With and without glass‐fiber

Abstract: The recycling possibilities of poly(butylene terephthalate)/polycarbonate/acrylonitrile-butadiene-styrene (PBT/PC/ABS) ternary blend with and without glassfiber content were investigated using repeated injection molding process. In this study, PBT/PC/ABS ternary blends were reprocessed at five times and the results were presented after each recycling process. The recycling possibility of PBT/PC/ABS ternary blend was evaluated by measuring the mechanical, chemical, thermal, and rheological properties. Mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…1); similar results were observed in the literature [1,10,16,17]. It was also found that molding conditions did not affect the characteristic bands of both virgin and recycled samples.…”
Section: Physical and Chemical Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…1); similar results were observed in the literature [1,10,16,17]. It was also found that molding conditions did not affect the characteristic bands of both virgin and recycled samples.…”
Section: Physical and Chemical Propertiessupporting
confidence: 92%
“…It was also found that molding conditions did not affect the characteristic bands of both virgin and recycled samples. FTIR peaks for PBT= PC=ABS ternary blends are summarized in Table 3 and results were compared with related studies [10,18].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…62% was recovered through recycling and energy recovery processes while 38% still went to landfill [1]. Many experts have done a lot of research on the recovery, using different polymeric materials [2][3][4][5][6]. While plastics are still preferred, one major issue is the recycling of polymeric materials in polymer technology, since it is important to control whether the recovered materials have the necessary properties, required for the reuse.…”
Section: Introductionmentioning
confidence: 99%